Digital health interventions for cancer-related cognitive impairment in breast cancer patients: A scoping review - Ying-Xiang Chen; You Zhou; Xiao-Lan Zhang; Wen-yan He; Qin Ye; Min Xu (Digital Health)
Background Breast cancer is a common malignancy among women worldwide, frequently associated with cancer-related cognitive impairment, which significantly affects quality of life. Non-pharmacological therapies, especially digital health interventions (DHIs), show potential in mitigating cognitive impairment related to cancer through tailored and interactive cognitive training. Nonetheless, current research fails to systematically integrate intervention strategies, behavioral change techniques (BCTs), and their effectiveness. Objective This scoping review sought to delineate existing DHIs for cognitive impairment related to cancer in breast cancer patients, emphasizing intervention attributes, efficacy, and the use of behavior change techniques to guide future research and clinical practice. Methods Following Arksey and O’Malley's framework, nine databases were systematically searched (inception to February 2025). Inclusion criteria were defined using PICOS (Population, Intervention, Comparison, Outcomes, Study design). Data on intervention characteristics, BCTs, and outcomes were extracted and analyzed via Michie's BCT taxonomy. Results Nineteen studies were incorporated. DHIs predominantly employed computerized cognitive training (78.94%), virtual reality (VR) (15.78%), and robotics (5.26%). Prominent BCTs encompassed goal setting (100%), feedback/monitoring (89%), and social support (100%). Eighteen investigations indicated substantial cognitive enhancement, six saw better emotional well-being, and two evidenced an elevated quality of life. Gamification and VR therapies resulted in elevated patient adherence and satisfaction. Conclusion DHIs significantly enhance Cognitive Rehabilitation and Cognitive Impairment through cognitive training and multifaceted BCTs. Challenges encompass diverse study designs, insufficient long-term data, and technical obstacles. Future research must include standardized cognitive evaluations, longitudinal investigations, and initiatives to address the digital divide.